2022
DOI: 10.1101/2022.01.27.22269941
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of SARS-CoV-2 nasopharyngeal testing in a rural community sample susceptible of first infection: the CHRIS COVID-19 study

Abstract: Background To rapidly characterize COVID–19 epidemiology, numerous population-based studies have been undertaken to model the risk of SARS–CoV–2 infection. Less is known about what may drive the probability to undergo testing. Understanding how much testing is driven by contextual or individual conditions provides the basis for unbiased representation of testing figures and shaping of public health interventions and resource allocation. Methods In the Val Venosta/Vinschgau district (South Tyrol, Italy), we co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…However, self-reported symptoms have shown greater breadth than electronic medical record-extracted symptoms 49. Moreover, another report on the same cohort21 showed that if participants were to experience symptoms they would generally be tested for COVID-19, limiting the possibility of testing bias in our results.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…However, self-reported symptoms have shown greater breadth than electronic medical record-extracted symptoms 49. Moreover, another report on the same cohort21 showed that if participants were to experience symptoms they would generally be tested for COVID-19, limiting the possibility of testing bias in our results.…”
Section: Discussionmentioning
confidence: 80%
“…We invited an age-sex stratified random sample targeting 1450 participants of the Cooperative Health Research in South Tyrol (CHRIS) study29 representative of all adult residents in the district to participate in the CHRIS COVID-19 prospective investigation between 13 July and 28 August 2020 20 21. An online screening questionnaire covered SARS-CoV-2-related anamnesis since 1 February 2020 until participation to the baseline clinical visit for blood drawing and testing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations